Making Gems in Indian Alchemical Literature - Wujastyk, Dagmar (History of Science in South Asia)

(untitled) (University of Alberta Library, 2023)
This article examines the practice of producing factitious gems as described in Nityanātha’s Jewel Mine of Mercury (Rasaratnākara), a thirteenth to fifteenth-century alchemical work written in Sanskrit. It queries how this practice fits within the Indian alchemical discipline and explores its possible connections with other artisanal crafts.